Komunikasi Persuasif Dan Koersif Niniak Mamak Kepada Anak Kemenakan Yang Kawin Sasuku : (Studi Kasus Suku Payobada Jorong Lakuak Dama Nagari Tanjung Haro Sikabu Kabu Padang Panjang Kecamatan Luak Kabupaten Lima Puluh Kota) - Muslim Muslim; Muhamad Fajri (STIKes Ibnu Sina Ajibarang, 2023)
The results that Niniak Mamak’s persuasive and coercive communication with sasuku’s married nephew (Case Study of the payobada Jorong Lakuak Dama Nagari Tanjung Haro Sikabu Kabu Padang Panjang Subdistrict, Luak District, Fifty Cities District), can be proven by the association conducted by Niniak Mamak to niece’s child, then Niniak Mamak communicated with her nephew regarding customs including the custom of prohibiting sasuku marriage for nephew’s children and mamak also conveyed what sanctions or punismants would be given to her nephew’s children if there was a nephew’s child who violated the prohibition against sasuku marriage. In addition, Niniak Mamak also appealed to her nephew’s children to comply with the cutomary rules set by Niniak Mamak in the Nagari For the good of the nephew’s children in the Nagari.